The shadows of poetry : Vergil in the mind of Augustine - MacCormack, Sabine (Berkeley : University of California Press, 1998)
Imperial ceremony was a vital form of self-expression for late antique society. Sabine MacCormack examines the ceremonies of imperial arrivals, funerals, and coronations from the late third to the late sixth centuries A.D., as manifest in the official literature and art of the time. Her study offers us new insights into the exercise of power and into the social, political, and cultural significance of religious change during the Christianization of the Roman w.
List of illustrations -- Preface -- I. "Their renowned poet" -- II. "The scent of a rose": Language and grammar between Pagans and Christians -- III. "The tears run down in vain": Emotions, soul, and body -- IV. "Gods of our homeland": The nature of true and false worship -- V. "The high walls of Rome": The city on Earth and the heavenly city -- Epilogue -- Select bibliography -- Index of ancient and late antique texts -- General index.
Earlier versions of three chapters were presented as a Christian Gauss Seminar in Criticism, Princeton University, winter of 1994.
Includes bibliographical references (pages 233-250) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Virgil; Augustine, -- of Hippo, Saint, -- 354-430 -- Literary style; Virgil -- Influence; Augustine, -- of Hippo, Saint, -- 354-430 -- Books and reading; Virgil; Augustine, -- Saint, Bishop of Hippo; Augustine, -- of Hippo, Saint, -- 354-430; Virgil; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Influence (Literary, artistic, etc.); Literary style; Religion; Philosophy & Religion; Christianity